Perancangan Poster Edukasi Sebagai Upaya Peningkatan Wawasan Tanaman Pada Wisata Agro Lembah Kecubung - Yassinta Fitria; Bayu Setiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The abundance of diverse and beautiful natural resources in a region is an invaluable wealth. Likewise with the PKKM MBKM Village Development program in Penanggungan Village, Trawas, Mojokerto. Apart from being designed to improve the implementation of the Independent Learning program in building a village, the main aim is to hone students' abilities in identifying, developing and empowering the potential of the village. One of them is the Agro Tourism Valley Kecubung which has just opened and requires strong branding to improve the image of the tourist attraction. So Village Development program students helped in the design efforts. One of which is designing educational posters